Respostas

2014-03-03T16:21:47-03:00
 ► PROGRESSÃO GEOMÉTRICA:

► Termo:

► Soma:
► S(n) = u0 * (1 - qⁿ)/(1 - q)

► u0: primeiro termo
► q: razão
► n: número de termos

► PG(1) = u0
► PG(2) = u0.q
► PG(3) = u0.q²
► PG(4) = u0.q³
► PG(5) = u0.q^4

► produto P = u0^5.q^10
► PG(4) + PG(5) = 12

► P = u0^5.q^10 = 32 = 2^5
► --> u0.q² = 2 (eq 1)

► PG(4) + PG(5) = 12
► u0.q³ + u0.q^4 = 12
► u0.q².(q+q²) = 12
► eq 1 --> 2.(q + q² = 12
► q + q² = 6
► q² + q - 6 = 0
► (q - 2)*(q + 3) = 0
► q' = 2
► q" = -3 não serve

► valor de u0
► eq 1 --> u0q² = 2
► u0.2² = 2
► u= = 2/4 = 1/2

► a PG é {1/2, 1, 2, 4, 8}

► verificação
 " P = 1/2 * 1 * 2 * 4 * 8 = 32
  soma dos dois últimos = 4 + 8 = 12 "